2002
DOI: 10.1080/00926230290001439
|View full text |Cite
|
Sign up to set email alerts
|

The Motivation and Mental Health of Sex Workers

Abstract: Commercial sex work presents specific mental health concerns. We aimed to study motivation for sex work and mental health issues in a sample of such women. We contacted 55 consenting women through organized brothels and interviewed them using the Farley questionnaire and screening items for posttraumatic stress disorder (PTSD) and depression. Eighty-two percent of the women had arrived illegally and had been "trafficked." All but 2 were engaged voluntarily in sex work. Seventeen percent met criteria for PTSD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 8 publications
3
57
1
2
Order By: Relevance
“…Moreover, in keeping with earlier data Chudakov et al, 2002;Farley & Barkan, 1998), our study reveals that female sex workers frequently consult health professionals with regard to mental health and drug addiction problems. The sex trade is illegal and is conducted underground, thus making sex-trade workers extremely vulnerable to violence and aggression from clients, brothel keepers, or spouses, and to fear problems with the police and the justice system.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, in keeping with earlier data Chudakov et al, 2002;Farley & Barkan, 1998), our study reveals that female sex workers frequently consult health professionals with regard to mental health and drug addiction problems. The sex trade is illegal and is conducted underground, thus making sex-trade workers extremely vulnerable to violence and aggression from clients, brothel keepers, or spouses, and to fear problems with the police and the justice system.…”
Section: Discussionsupporting
confidence: 89%
“…For example, several interviewees explained an aspect of drug and alcohol use and sex work particular to SWM: being forced to have sex with a man or a woman despite their sexual orientation or partner preference. The negative physical and emotional consequences of sex work, including violence, depression, and sexually transmitted infections, are well-documented globally (Chudakov, Ilan, Belmaker, & Cwikel, 2002;Miller, Lao, Wagner, & Korves, 2008), but the impact of having sex with a man for money when one would not normally engage in sexual relations with men is an additional and under-discussed physical and emotional health challenge for SMW sex workers. SMW like Kayla may not worry about sexual risks in their current relationship with a woman, but may fail to consider or recognize the risks that they brought into the relationship via sex work.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has already suggested that patients' psychosocial needs are one of the underlying determinants of health, including STI/HIV prevention (Chudakov et al 2002;Sobel 1995). Women who are trading sex for drugs, money, or items of daily living are unlikely to have the means to pay for therapy.…”
Section: Discussionmentioning
confidence: 99%